Failure of trehalose-6,6'-dimycolate (P3 or cord factor) to enhance endotoxin lethality in mice. - Yarkoni, E (1976)
The increased endotoxin lethality in mice pretreated with BCG was not observed in mice pretreated with trehalose-6,6'-dimycolate instead of BCG.